Posttransplant Outcomes for cPRA-100% Recipients Under the New Kidney Allocation System. Issue 7 (July 2020) - Jackson, Kyle R.; Holscher, Courtenay; Motter, Jennifer D.; Desai, Niraj; Massie, Allan B.; Garonzik-Wang, Jacqueline; Alachkar, Nada; Segev, Dorry L.
Abstract : Background: There is concern in the transplant community that outcomes for the most highly sensitized recipients might be poor under Kidney Allocation System (KAS) high prioritization. Methods: To study this, we compared posttransplant outcomes of 525 pre-KAS (December 4, 2009, to December 3, 2014) calculated panel-reactive antibodies (cPRA)-100% recipients to 3026 post-KAS (December 4, 2014, to December 3, 2017) cPRA-100% recipients using SRTR data. We compared mortality and death-censored graft survival using Cox regression, acute rejection, and delayed graft function (DGF) using logistic regression, and length of stay (LOS) using negative binomial regression. Results: Compared with pre-KAS recipients, post-KAS recipients were allocated kidneys with lower Kidney Donor Profile Index (median 30% versus 35%, P < 0.001) but longer cold ischemic time (CIT) (median 21.0 h versus 18.6 h, P < 0.001). Compared with pre-KAS cPRA-100% recipients, those post-KAS had higher 3-year patient survival (93.6% versus 91.4%, P = 0.04) and 3-year death-censored graft survival (93.7% versus 90.6%, P = 0.005). The incidence of DGF (29.3% versus 29.2%, P = 0.9), acute rejection (11.2% versus 11.7%, P = 0.8), and median LOS (5 d versus 5d, P = 0.2) were similar between pre-KAS and post-KAS recipients. After accounting for secular trends and adjusting for recipient characteristics, post-KAS recipients had no difference in mortality (adjusted hazard ratio [aHR]: 0.86 1.623.06, P = 0.1), death-censored graft failure (aHR: 0.52 1.001.91, P > 0.9), DGF (adjusted odds ratio [aOR]: 0.58 0.861.27, P = 0.4), acute rejection (aOR: 0.61 0.941.43, P = 0.8), and LOS (adjusted LOS ratio: 0.98 1.161.36, P = 0.08). Conclusions: We did not find any statistically significant worsening of outcomes for cPRA-100% recipients under KAS, although longer-term monitoring of posttransplant mortality is warranted.